2010
DOI: 10.3201/eid1608.091931
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic (H1N1) 2009 Virus and Down Syndrome Patients

Abstract: We compared prevalence of hospitalization, endotracheal intubation, and death among case-patients with and without Down syndrome during pandemic (H1N1) 2009 in Mexico. Likelihoods of hospitalization, intubation, and death were 16-fold, 8-fold, and 335-fold greater, respectively, for patients with Down syndrome. Vaccination and early antiviral drug treatment are recommended during such epidemics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 12 publications
1
66
0
5
Order By: Relevance
“…This can lead to severe respiratory syncytial virus bronchiolitis, a frequent cause of hospitalization in DS children (10,(26)(27)(28). Also, an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection was reported in DS (29). In addition, we found an increased proinflammatory cytokine response to live influenza A virus in children with DS, which might contribute to an increased severity of their clinical course of this infection (30).…”
mentioning
confidence: 61%
“…This can lead to severe respiratory syncytial virus bronchiolitis, a frequent cause of hospitalization in DS children (10,(26)(27)(28). Also, an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection was reported in DS (29). In addition, we found an increased proinflammatory cytokine response to live influenza A virus in children with DS, which might contribute to an increased severity of their clinical course of this infection (30).…”
mentioning
confidence: 61%
“…We chose to consider these conditions because they represent a wide spectrum of chronic diseases in terms of morbidity, mortality and pattern of contacts with different health providers, and because they experience frequent complications during influenza [4-9]. Moreover the selected study population includes children affected with diseases that may be perceived with different levels of severity: this may affect the frequency of recommendations and immunization coverage.…”
Section: Methodsmentioning
confidence: 99%
“…HIV-infected children and adolescents, especially persons with a low CD4 cell count or AIDS, can experience more severe complications of seasonal influenza [8]. High rates of influenza-associated complications and death have been reported in children with Down syndrome [9]. …”
Section: Introductionmentioning
confidence: 99%
“…This can lead to severe RSV bronchiolitis which in its turn is a frequent cause of hospitalization in DS children [7][8][9][10]. Very recently, it was shown that children with DS also have an increased risk of hospitalization, endotracheal intubation, and death due to influenza A virus infection [11].…”
Section: Introductionmentioning
confidence: 98%